Pengaruh Pengendalian Internal & E-Procurement Terhadap Fraud: (Studi kasus pada Dinas Pendapatan dan Pengelolaan Keuangan dan Aset Daerah, dan Inspektorat Kabupaten Bandung Barat) - Inta Budi Setya Nusa (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Supervision, control and coordination have not been adequate in the asset management area is the cause of the occurrence of fraud at the Department of revenue and the financial and assets Management area of West Bandung Regency factors led to fraud is the auction process that is not in accordance with the rules of procurement of goods and services electronically. The purpose of this study is to analyze and assess influence of internal controls against fraud and E-procurement against fraud. The methods used in this research is descriptive method and verifikatif. The descriptive method was used to find out the description of the variable Internal control, variable E-procurement and Fraud. To know the influence of Internal control variables and variable E-procurement against Fraud done with test statistics. The statistical test used was the structural model design, design a model of measurement, line diagrams, test the fit of the model. Test the fit of the structural model and hypotheses using the software Smart PLS 2.0. M3. The Unit of analysis in this research was an employee of Department of Revenue and the financial management and internal Auditors and regional Assets Inspectorate West Bandung Regency. The research results showed that internal control influential high enough against Fraud and E-procurement influential high enough against fraud, on the Department of revenue and the financial and assets Management area of West Bandung Regency.